2009
DOI: 10.3750/aip2009.39.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Koi Herpes Virus: Do Acipenserid Restitution Programs Pose a Threat to Carp Farms in the Disease-Free Zones?

Abstract: Background. Sturgeons have long been extinct in Polish inland waters. A substantial effort has recently been put into their restitution, covering the drainage areas of two major Polish rivers, the Oder and the Vistula. The stocked fishes are clinically healthy, but very little is known about their potential to transmit viral diseases including koi herpes virus (KHV) to healthy fishes of other species, which may pose a threat to the disease-free zones. This study was intended to determine if sturgeons could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 4 publications
3
40
2
Order By: Relevance
“…The total number of positive fish detected by nested PCR is listed in Table 1. Kempter et al (2009) reported that Atlantic sturgeon and Russian sturgeon are susceptible to CyHV-3; similarly, we found sterbel to be positive for CyHV-3 DNA. The susceptibility of stone loach (previously member of family Cobitidae, now Balitoridae) might suggest that species of the family Cobitidae could be generally susceptible to CyHV 3; for instance, Kempter et al (2012) reported susceptibility of spined loach.…”
Section: Original Papersupporting
confidence: 57%
“…The total number of positive fish detected by nested PCR is listed in Table 1. Kempter et al (2009) reported that Atlantic sturgeon and Russian sturgeon are susceptible to CyHV-3; similarly, we found sterbel to be positive for CyHV-3 DNA. The susceptibility of stone loach (previously member of family Cobitidae, now Balitoridae) might suggest that species of the family Cobitidae could be generally susceptible to CyHV 3; for instance, Kempter et al (2012) reported susceptibility of spined loach.…”
Section: Original Papersupporting
confidence: 57%
“…The fact that the disease has never been found within other fish than C. carpio, namely in common carp and koi, did not detract from the ------------1 21 st 29 -32 + -+ -----+ 2 -------28 28 -+ + 3 29 -30 + -+ 31 29 29 + + + 4 31 --+ --30 28 28 + + + 5 28 --+ ------- possibility of virus replication in other fish species and investigations were not conducted to investigate the role of KHVD transmission through vector fish species, i.e., its transfer as an infectious agent to naive carp detected by a combination of virological and serological methods other than in carp or koi [38]. It has since been found that a lot of other fish species such as goldfish, crucian carp, different sturgeon species, grass carp (Ctenopharyngodon idella), silver carp (Hypophthalmichthys molitrix) or tench (Tinca tinca) may be act as a healthy appearing carrier hosts which can transfer the KHV to naive carp or koi [22,24,26,27,39]. KHVD has never occurred in any of those fish species when inoculated with KHV.…”
Section: Discussionmentioning
confidence: 99%
“…For CyHV-3 or koi herpesvirus (KHV), although KHV disease (KHVD) is induced only in the species C. carpio (common carp and koi), it has been demonstrated that this virus can be present, and sometimes replicated, in a lot different fish species living in fresh and brackish water. KHV DNA has been identified by different PCR methods in a lot of members of the families Acipenseridae [22], Cyprinidae, including common carp or koi hybrids [23][24][25], and Percidae in many wild fish populations within close vicinity to, or in carp ponds [26,27]. Furthermore KHV has also been detected in fresh water mussels and crustaceans [28].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrids of goldfish and carp or koi are also susceptible to experimental infection of KHV [8,35]. KHV has been detected by PCR in Russian sturgeon and Atlantic sturgeon from fish farms in Northern Poland [44]. Susceptible host range of KHV and its nature of infection in different fish species are shown in Table 2.…”
Section: Koi Herpes Virus Disease (Khvd)mentioning
confidence: 99%